2023
DOI: 10.1007/s12035-023-03424-6
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Brain Health: Midlife Ovarian Removal Affects Associative Memory

Abstract: Women with early bilateral salpingo-oophorectomy (BSO; removal of ovaries and fallopian tubes) have greater Alzheimer’s disease (AD) risk than women in spontaneous/natural menopause (SM), but early biomarkers of this risk are not well-characterized. Considering associative memory deficits may presage preclinical AD, we wondered if one of the earliest changes might be in associative memory and whether younger women with BSO had changes similar to those observed in SM. Women with BSO (with and without 17β-estrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 65 publications
0
0
0
Order By: Relevance
“…That similar right-lateralized areas of higher GM volume were not observed for either the BSO or the BRCA-preBSO groups suggests that postsurgical ERT may play a role in this plasticity. 61 Additionally, areas of higher GM volume were observed in right subcortical structures, including thalamus, putamen, and caudate, as well as extensively in bilateral cerebellum. Postmortem ER mapping in humans has indicated that structures like the putamen and caudate do not have high densities of ERs, suggesting that even without obvious structural changes, the brain may be recruiting those areas less affected by the sudden postsurgical E 2 loss in an effort to preserve function.…”
Section: Discussionmentioning
confidence: 95%
“…That similar right-lateralized areas of higher GM volume were not observed for either the BSO or the BRCA-preBSO groups suggests that postsurgical ERT may play a role in this plasticity. 61 Additionally, areas of higher GM volume were observed in right subcortical structures, including thalamus, putamen, and caudate, as well as extensively in bilateral cerebellum. Postmortem ER mapping in humans has indicated that structures like the putamen and caudate do not have high densities of ERs, suggesting that even without obvious structural changes, the brain may be recruiting those areas less affected by the sudden postsurgical E 2 loss in an effort to preserve function.…”
Section: Discussionmentioning
confidence: 95%
“…Premenopausal bilateral oophorectomy (PBO) causes abrupt endocrine dysfunction (e.g., loss of estrogen, progesterone, testosterone, and an increase in gonadotropins). Studies suggest that females with PBO are at an increased risk of cognitive impairment and dementia, 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 but few neuroimaging studies have been conducted to clarify the underlying pathogenesis. One small study reported PBO was associated with smaller amygdala volume, thinner parahippocampal‐entorhinal cortex, and lower entorhinal white matter fractional anisotropy (FA) compared to referent females.…”
Section: Introductionmentioning
confidence: 99%